Evil and Politics: The Possibility of Response to Evil and Its Limits. The Case of Eichmann Trial - Merkinaitė, Simona (Politologija, 2021)
The legal challenges arising from the Adolf Eichmann trial in Jerusalem are widely discussed in legal theory. Less attention is given to the trial in the framework of political and moral philosophy, where the key focus remains on the nature and the origins of evil (without a doubt, fuelled by Hannah Arendt’s definition of banality of evil). However, the trail itself present equally challenging question of human response to evil: how are we, the members of the modern political locus to respond to the evil of inhuman proportions? This article aims to answer the question through the reconstruction of debate that took place during the period of the trail (from the date of capture of Eichmann in 1960, till his execution in 1962) and the arguments “for” and “against” the trial by Arendt, Karl Jaspers, Isaiah Berlin, Gershom Scholem and Martin Buber. Beyond these arguments, there is an engaging philosophical debate about the nature and origins of justice, the limits of guilt and retribution, crime and punishment. It is argued that Arendt’s pro-trail stance provide for a way of engagement with the questions of evil by modern political men.